FACTORS RELATED TO GASTRITIS EVENTS IN ADULTS (26 - 45 YEARS) IN RT 002/RW 004 BEACH MEKAR VILLAGE - Tiara, Tiara Nur Safitri; Meliyana, Ernauli; Dinda Nur Fajri Hidayati Bunga (Rena Cipta Mandiri, 2024)
Gastritis can affect all age levels, the most common age of gastritis is adulthood, this adult age ranges the productive age range that does more activities. Gastritis is a disease that occurs due to inflammation of an acute and chronic nature. The impact of gastritis can interfere with daily activities due to the appearance of several complaints such as pain in the liver, burning, nausea, vomiting, weakness, no appetite, Gastritis has many factors, including irregular diet, infection with helicobacter pylori germs, the habit of consuming coffee, cigarettes. This research method is quantitative research using analytical observational and using a crossectional approach. The population in this study was residents of RT 002/ RW 004 Pantai Mekar Village as many as 100 respondents, the sample technique used was simple random sampling, bivariate analysis using the Chi Square statistical test. Based on the results of the Chi Square statistical test, a dietary factor p value (0.031) < a value of α (0.05) H1 was received, a coffee consumption factor p value (0.002) < a α value (0.05) H1 was received, a smoking factor p value (0.770) > a α value (0.05) H1 was rejected. Based on the results of the study there is a relationship of dietary factors with the incidence of gastritis, there is a relationship of coffee consumption factors with the incidence of gastritis, there is no relationship of smoking factors with the incidence of gastritis